Indicators of physical abilities in students of education secondary developed by the strengthening plan of physical education and school sport Puno 2016 - Maquera Maquera, Yanet Amanda (2017)
The purpose of this study was to determine the indicators of physical abilities (speed, agility, strength, endurance and flexibility) in a population of 280 students (13 to 17 years of age) of secondary education, subject to First level of intervention of the Plan to Strengthen Physical Education and School Sport, at the educational institution Glorioso San Carlos in the city of Puno. The results show that, the performance indicators in the different physical capacities rise in a progressive and moderate way, placing 67.36% in the middle category, in general. It is concluded that it is not sufficient to define the results of the physical capacity indicators, based on the application of a single measurement instrument; It is also not appropriate, to start with speed as a basis for developing other physical abilities, but from strength, designing learning plans that provide the student with the appropriate amount of time and physical exercise, to obtain maximum performance with The minimum risk, respectively.